The Braille Painting for Children Education: An Ecofeminism Studies - Probosiwi Probosiwi (IJCAS (International Journal of Creative and Arts Studies), 2017)
Braille painting which Niken Larasati’s artwork is one of the visual art medium for learning children, especially those with special needs (diffable), but this work can also be enjoyed by all people. The medium used is cowhide carved and color. The basic principle of this work is the creation of a child's world that is filled with joy, innocence, excitement packed in play activities. This work as a form of education to children with sensitivity to sensory owned by touching, feeling, speech, movement, and even combine elements of science in it as counting activities. In addition, children are required to interact with and respond to a group of playmates, natural conditions, verbal strength training, even rough motoric and fine motoric. Contextual studies using educational theory Humanistic by Abraham H. Maslow, and finding textual studies using the theory of Nature Ecofeminism by Susan Griffin. This type of research is qualitative to understand the phenomenon or text that occurs on the object study such behavior, perception, motivation, and other actions holistic, descriptive on the specific context of natural and utilize natural methods.